Nurses on the Move: Migration and the Global Health Care Economy - Margaret Keatings (Nursing Leadership, 2006)
by Mireille Kingma 288 pages, Cornell University Press US$24.95 paper, US$49.95 cloth Administrators and nursing leaders understand the need for strategies to address the anticipated global nursing shortage and ensure the quality and safety of patient care now and into the future. Understanding, however, does not necessarily translate into action. Worldwide, nurses continue to face challenges in the work environment, economically, socially and, sometimes, politically. For some, migration has seemed a solution; others see it as part of the problem.